2014
DOI: 10.1080/00273171.2013.836621
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Individualism, Nationalism, Ethnocentrism, and Authoritarianism in Flanders: A Continuous Time-Structural Equation Modeling Approach

Abstract: This article analyzes the relationships among nationalism (N), individualism (I), ethnocentrism (E), and authoritarianism (A) in continuous time (CT), estimated as a structural equation model. The analysis is based on the General Election Study for Flanders, Belgium, for 1991, 1995, and 1999. We find reciprocal effects between A and E and between E and I as well as a unidirectional effect from A on I. We furthermore find relatively small, but significant, effects from both I and E on N but no effect from A on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Conversely, the country's political ideology towards multiculturalism indicates a strong preference for migrants to assimilate rather than to integrate, as heritage culture maintenance is often perceived as a threat to the country's social harmony (Deaux, 2006;Hero & Preuhs, 2006). Moreover, the American national culture stresses individualism (Hofstede, 2001), which has been found to be positively correlated with ethnocentrism (Angraini, Toharudin, Folmer, & Oud, 2014). Due to this mixed perception of multiculturalism in the USA, we predicted that the associations between national culture maintenance with ethnorelativism (Hypothesis 4) and ethnocentrism (Hypothesis 5) would be non-significant or weaker than the association of multicultural adaptation with ethnorelativisim and ethnocentrism, supporting discriminant validity of the Multi-VIA (Field, 2009;Trochim & Donnelly, 2007).…”
Section: Convergent and Discriminant Validity: Ethnocentrism Vs Ethnmentioning
confidence: 99%
“…Conversely, the country's political ideology towards multiculturalism indicates a strong preference for migrants to assimilate rather than to integrate, as heritage culture maintenance is often perceived as a threat to the country's social harmony (Deaux, 2006;Hero & Preuhs, 2006). Moreover, the American national culture stresses individualism (Hofstede, 2001), which has been found to be positively correlated with ethnocentrism (Angraini, Toharudin, Folmer, & Oud, 2014). Due to this mixed perception of multiculturalism in the USA, we predicted that the associations between national culture maintenance with ethnorelativism (Hypothesis 4) and ethnocentrism (Hypothesis 5) would be non-significant or weaker than the association of multicultural adaptation with ethnorelativisim and ethnocentrism, supporting discriminant validity of the Multi-VIA (Field, 2009;Trochim & Donnelly, 2007).…”
Section: Convergent and Discriminant Validity: Ethnocentrism Vs Ethnmentioning
confidence: 99%
“…Apart from this, nationalism is usually seen as an ideology with more abundant meaning than ethnocentrism (Freeden, 1998). Researchers regard ethnocentrism as a critical contributor to nationalism (Bizumic and Duckitt, 2012) and have found that ethnocentrism positively predicts nationalism (Angraini et al, 2014). Considering the previous research findings that disgust can predict ethnocentrism, we think there is a connection between disgust and nationalism.…”
Section: Introductionmentioning
confidence: 67%
“…The development of new estimation packages means that the application of the CT modeling approach has never been easier (Boker et al, 2004;Boker, Deboeck, et al, 2010;Ou et al, 2017). The call for a more widespread adoption of CT models is matched by a growing number of applications of these models in substantive areas (e.g., Toharudin et al, 2008;Boker, Montpetit, et al, 2010;Steele & Ferrer, 2011;Angraini et al, 2014;Chow et al, 2018). For many researchers, however, a knowledge gap remains:…”
Section: Discussionmentioning
confidence: 99%